MITIGATIVE EFFECT OF DIVERSE USE OF NITROGEN SOURCES ON BULK DENSITY, ORGANIC MATTER AND GRAIN YIELD OF HYBRID MAIZE - M. Waseem; A. Ali; M. Tahir; K. Mehmood (Journal of Animal and Plant Sciences, 2013)
A number of factors are responsible for low yield of maize. Inappropriate crop nutrition management and poor soil fertility are the most important than others. Two year field trail was conducted to determine the mitigative effect of diverse use of nitrogen sources on bulk density, organic matter and grain yield of hybrid maize (Zea mays L.) at the Agronomic Research Area, University of Agriculture, Faisalabad during autumn 2008 and 2009. Experiments were laid out in a randomized complete block design (RCBD) with factorial arrangement having 3 replications with a net plot size of 3m x 5m. Treatments comprised two hybrids:H1 (Pioneer-30Y87) and H2 (Pioneer-31R88) with combination of six nitrogen sources S0: Control (0) kg N ha-1 , S1:Urea (50%) + Poultry manure (50%), S2: Urea (50%) + Farm Yard Manure (50%) , S3: Urea (50%) + Pressmud of sugarcane manure (50%), S4: Urea (50%) + Compost (50%), S5: Urea (50%) + (PM+FYM+PMS+ Compost) 50% . The hybrid maize varieties showed no significant effect on bulk density and organic matter for 2008 and 2009. The effect of nitrogen sources was significant in both seasons for bulk density and organic matter. Bulk density maximum in S0: Control (0) kg N ha-1 treatment where no nitrogen applied and minimum in S1: Urea (50%) + Poultry manure (50%) treatment combination while antagonistic effect was observed for organic matter. Hybrid maize H1(Pioneer - 30Y87) produced better grain yield (6.14 t ha-1) during 2008 when nitrogen sources S1: Urea (50%) + Poultry manure (50%) was applied in combination as compared to grain yield (6.08 t ha-1) in hybrid H2 (Pioneer -31R88) during 2009. While maximum grain yield (7.05 t ha-1 ) and (6.92 t ha-1) was found in nitrogen sources S1: Urea (50%) + Poultry manure (50%) treatment combination in 2008 and 2009 as compared to minimum grain yield (3.73 t ha- 1) where no nitrogen applied (S0 : Control 0 kg N ha-1 ) treatment, respectively.
Keywords: Nitrogen sources; Hybrid maize; Grain yield; Bulk density; Organic matter